2019
DOI: 10.4103/jmu.jmu_70_18
|View full text |Cite
|
Sign up to set email alerts
|

Role of orbital ultrasound in the assessment of clinically detected papilledema

Abstract: Background:Increased intracranial pressure (ICP) is frequently seen, and it is considered a serious problem that needs a careful assessment and management, especially by easy and least invasive modalities.Objective:The objective of the study is to assess the optic nerve sheath diameter (ONSD) using transorbital ultrasound (US) as a marker and indicator for diagnosing raised intracranial pressure.Patients and Methods:It is a prospective study that was carried out in Neurology and/or Ophthalmology Clinics, Baghd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…A previous study found an elevated optic disc when using ultrasound to measure the ONSD to evaluate ICP and used the presence or absence of the optic disc as the basis for the diagnosis of elevated ICP. Although the specificity of the diagnosis was 100%, the sensitivity was only 41.6% (Mohson and Auday, 2019). In our study, ODH was specifically measured, and the sensitivity and specificity were 73% and 83%, respectively.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…A previous study found an elevated optic disc when using ultrasound to measure the ONSD to evaluate ICP and used the presence or absence of the optic disc as the basis for the diagnosis of elevated ICP. Although the specificity of the diagnosis was 100%, the sensitivity was only 41.6% (Mohson and Auday, 2019). In our study, ODH was specifically measured, and the sensitivity and specificity were 73% and 83%, respectively.…”
Section: Discussionmentioning
confidence: 53%
“…A growing body of research has begun to identify more markers that may assist in the assessment of high intracranial pressure and thus improve the accuracy of the assessment of high intracranial pressure. In addition to measuring the ONSD and identifying the optic disc bulge, ocular ultrasound has indicated a further marker, the crescent sign, which is less sensitive but has high specificity (100%) (Mohson and Auday, 2019). A recent study showed that the deformability index (DI) is a dynamic parameter that quantifies the pulsatile nature of optic nerve sheaths and can distinguish between patients with elevated and normal ICP.…”
Section: Discussionmentioning
confidence: 99%
“… Komut 2016 [ 21 ] Turkey Prospective 50 5.4 Toshiba Aplio 500 Platinum ED CT Mixed 3 mm proximal to the optic disc; in transverse and sagittal planes. Mohson 2019 [ 22 ] Iraq Prospective 40 5.6558 Philips HD11XE Clinic LP Mixed 3 mm posterior to the globe; transverse. Moretti 2009 [ 23 ] Italy Prospective 19 6.2 Hitachi EUB 405 ICU Inv Trauma 3 mm behind the globe; one sagittal and one transverse.…”
Section: Resultsmentioning
confidence: 99%
“…9 In the study of Teismann et al, 10 an optic disc elevation greater than 1.0 mm predicted optic disc edema, with a sensitivity of 73% and a specificity of 100%. Mohson et al 11 showed that the presence of optic disc bulging, without measuring its elevation, has a sensitivity of 61.1% and specificity of 100% for the detection of IH. It is important to take into account that the presence of papilledema may be due to other causes such as inflammatory diseases, infection, infiltrative conditions, and microvascular infarction.…”
Section: Discussionmentioning
confidence: 99%